Biocarvão e calcário como condiconadores de solos cultivados - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Soil conditioners maintain or improve soil quality and although they have limited amounts of nutrients, they have a benefic impact on soil physicochemical and biological attributes. Biochar and limestone, due to their chemical composition, are capable of improving soil attributes, by reacting at various hierarchical levels with organic matter and soil particles, directly influencing soil quality. In this context, the general objective of this study was to evaluate the effects application of these conditioners, on soil physicochemical and biological attributes, and for that, two different experiments were installed: (i) on a typical dystrophic RED-YELLOW LATOSOL, with a low biochar dose application associated with fertilization levels, in eucalyptus forest production, with the evaluation of physicochemical and biological attributes, in a short time (11 months), and, (ii) an HAPLIC aluminic CAMBISOL, with three lime doses application, in three incorporation forms, elapsed six years after the first liming. The treatments for the Latosol were biochar presence or absence, at 3,23 Mg ha-1, associated with three eucalyptus fertilization levels (FP = 100% of standard fertilization, FR = 80% of standard fertilization and SF = without fertilization), in two repetitions per plot. The Cambisol received three doses capable of raising base saturation by 50, 70 and 90% and a control area, without limestone, associated with incorporation forms (CIAG = limestone incorporated with plow and harrow, CIEG = limestone incorporated with chisel and harrow, and CSI = limestone without incorporation), in four repetitions. Undisturbed soil samples were collected in: (a) monoliths, in layers 0-0,1 and 0,1-0,2m, to assess the visual evaluation of soil structure quality (VESS), tensile strength, friability and aggregate stability; and in (b) volumetric rings, in layers 0-0,1 and 0,1-0,2m, to assess soil density (Ds) and total porosity (Pt). The deformed samples were collected in the same layers as volumetric rings, to determine soil acidity components (pH and Al3+), CTC and V%, exchangeable basic cations (Ca2+, Mg2 + and K+) and labile carbon (CL) contents, total organic carbon (TOC) and carbon stock (EC). The data were subjected to variance analysis, and when significant, the means were compared by Dunnett at 5% in Latosol, and the means test by Tukey at 5% in Cambisol. The results showed that in Latosol experiment, for most indicators there was no significant effect of treatments on soil quality. As a result, in Cambisol, it was observed that the highest limestone doses did not always favor the evaluated attributes and the CSI favored few evaluated attributes. Thus, it was concluded that biochar effect on Latosol quality indicators, under a perennial system, in eucalyptus planting, in the short term and in a reduced dose, were minimal; and in Cambisol, CIAG prevents on surface lime overdose, avoiding chemical stratification, consequently root stratification, biological stratification and finally physical stratification of soil profile.
Keywords: Agregação; Biocarvão; Calcário; Formas de incorporação de calcário; Níveis de fertilização; Qualidade do solo; Aggregation; Biochar; Limestone; Forms of limestone incorporation; Fertilization levels; Soil quality; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA